Beyond the 'official' religions: A normative framework for religious recognition in Indonesia - Iman Pasu Purba; Thohir Luth; Tunggul Anshari Setia Negara; Nur Chanifah (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
The regulation of religious recognition in Indonesia remains problematic to this day. Research on the regulation of religious recognition has not been conducted to date. As a country with diverse religions, Indonesia faces unique challenges in managing religious life for substantive citizenship. The terminology of "recognised" and "unrecognised" religions, as well as "official" and "unofficial" religions, is one of the factors that hinder the fulfilment of the right to religious freedom for Indonesian citizens. The regulation of religious recognition in Indonesia must address significant legal issues to achieve justice and legal certainty. Inclusive reforms, policy harmonisation, and stronger enforcement mechanisms are essential to ensure that all religious groups are treated equally under the law. These efforts must align with both constitutional principles and international human rights standards to uphold justice and legal certainty in the recognition of religion. Religious recognition must be in line with the spirit of the Indonesian nation, which upholds respect for human dignity, guarantees freedom of religion and belief, and upholds equality, non-discrimination, justice, and legal certainty. This paper is the result of normative research on the regulation of religious life in Indonesia, particularly regarding the recognition of religions in the country. The study concludes that, to date, there is no comprehensive regulation regarding the recognition of religions in Indonesia. Therefore, in the future, the formulation of such regulations is an urgent necessity. The regulation of religious recognition must prioritise the principles of equality, justice, and legal certainty. Indonesia needs fair religious recognition and legal certainty based on Pancasila